Impact of Effective Out Sourcing on Procurement Contract Performance: A Case Study of Kisoro District Local Government. - Ndayisenga, Jack (Kabale University., 2024)
The study was about establishing the effective outsourcing could lead to procurement contract performance. A case study of Kisoro District Local Government. The study was guided by three objectives which were to examine the impact of reasonable pricing on cost influence, to establish the impact of flexibility on the reliability of procurement contract performance, and to measure the relationship between experience and credentials on quality services of procurement contract performance. A targeted population of 55 respondents was considered for the study. These included 1 CAO, 2 Procurement officers, 2 personnel officers, 2 accounting officers, and 55 clients. Both simple random and purposive sampling techniques were used in identifying the study sample size. The methods that were used in data collection included questionnaires, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. Based on the results from the study, 100% of the respondents agreed that Kisoro district local government experiences reasonable pricing on cost influence in local government and these included marketing mix, product differentiation, product cost, market demand of a product, prices are required to be competitive, demand and utility of consumer, marketing method used. The study findings revealed the impact of flexibility on the reliability of procurement contract performance in local government and these included resilience from supply challenges comes from attacking supply chain constraints from all angles and having operational, enterprises should do more to prevent fraud by actively evaluating and estimating the obstacles that may be encountered in the process of execution, sourcing flexibility has many advantages as they help to the buying firm to reduce their backorders, shortcomings in the contract management process occur because the buyer and the supplier are two different entities. From objective three, it was found that the relationship between experience and credentials on quality services of procurement contract performance and these included procurement and contract management can be a daunting task for businesses, contract, and Project managers must be highly detail-oriented, monitoring and guiding the process to completion, project management is concerned with managing the activities required to complete a project successfully.